Example of negative energy density in a classical electron model. Issue 11 (November 2022) - Christensen, Nelson
Abstract: Classical models of the electron have been predicted to have negative rest energy density in certain regions. Using the model of the electron by Blinder we show that there are regions containing negative energy density, although the integral of the energy density over all space gives the electron rest mass. If the spin of the electron is ignored, then all regions of space have positive energy density with the Blinder model. The existence of Poincaré stress for the Blinder model is also demonstrated. The classical model for the electron discussed here admittedly does not involve quantum electrodynamics, where the infinite self energy is made finite with renormalization methods. Highlights: Classical model for the electron. Electron mass from electromagnetic energy. Region of negative energy density. Poincaré stresses. Abstract : Classical electron models; General relativity; Negative energy density